Sustainability in Industry 4.0 - Sapna; Gupta, Anjali (Ushus Journal of Business Management, 2022)
Industry 4.0 is considered the fourth industrial revolution. It is becoming a cutting-edge research topic among Academicians, industrialists, politicians and scientists. Researchers are focussing on the relationship between sustainability and industry 4.0 nowadays. The first part of this chapter will discuss how industry 4.0 can achieve sustainable development. The next part of this chapter concerns how green Labour markets can be digitised in industry 4.0. The smart technology of industry 4.0 helps in optimum utilisation of resources and reduction of waste. The social implication of industry 4.0 includes Employment generation and skill development. The main sustainability drivers of industry 4.0 are economic, environmental and social benefits. Transformation of industry 4.0 aimed towards achieving sustainable development, which is the need of the hour currently due to scarcity of resources. However, this transformation of industry 4.0 is a complicated and gradual process.